Adjuvant chemotherapy after neoadjuvant chemoradiation and curative resection for rectal cancer: Is it necessary for all patients?. Issue 4 (9th December 2014) - Jung, Kyung Uk; Kim, Hee Cheol; Park, Joon Oh; Park, Young Suk; Park, Hee Chul; Choi, Doo Ho; Cho, Yong Beom; Yun, Seong Hyeon; Lee, Woo Yong; Chun, Ho‐Kyung
<x xml:space="preserve">Abstract</x> Background The benefit of adjuvant chemotherapy for patients with locally advanced rectal cancer who have received neoadjuvant concurrent chemoradiation therapy (CCRT) and undergone curative resection remains unclear. Methods This study was a retrospective review of prospectively collected data. Patients with locally advanced rectal cancer who underwent curative surgery after neoadjuvant CCRT between January 2006 and March 2011 were identified. Four hundred forty‐one patients who completed adjuvant chemotherapy (chemo group) were compared with 35 patients who did not receive any adjuvant treatment (nonchemo group). Results The 5‐year disease‐free survival (DFS) was significantly higher in the chemo group (78.5% vs. 63.1%, P = 0.016). After stratification of the patients according to nodal status, these differences were no longer significant, but there were trends toward inferior DFS in the nonchemo group in all survival curves. In multivariate Cox regression analysis, no adjuvant chemotherapy (HR, 2.306; 95% CI, 1.101–4.829; P = 0.027) emerged as an independent prognostic factor associated with decreased DFS. Conclusions Adjuvant chemotherapy was significantly associated with increased DFS among patients who had undergone neoadjuvant CCRT and radical resection for locally advanced rectal cancer. Adjuvant chemotherapy should be considered in every patient after neoadjuvant CCRT irrespective of the final pathology stage. J. Surg. Oncol. 2015 111:439–444. © 2014 Wiley Periodicals, Inc.